Impact of effective connectivity within the Papez circuit on episodic memory: moderation by perivascular space function - Ling-Ling Li; Jie Ma; Jia-Jia Wu; Xin Xue; Mou-Xiong Zheng; Xu-Yun Hua; Qi-Hao Guo; Jian-Guang Xu (Alzheimer’s Research & Therapy)
Abstract Background and objectives The formation and retrieval of episodic memory is dependent on the coordinated activity of multiple brain regions and neural networks, with the Papez circuit playing a critical role in this process. Recently, the role of the perivascular space (PVS) in cognitive function has garnered increasing attention. However, the role of PVS function between neural circuits and cognitive function in amnestic mild cognitive impairment (aMCI) patients remains unknown. Therefore, this study aims to (1) investigate alterations in the effective connectivity of the Papez circuit and PVS function in patients with aMCI and (2) explore the role of PVS function between the effective connectivity of the Papez circuit and episodic memory. Methods Sixty participants, all of whom underwent multimodal MRI (fMRI, dMRI, and sMRI) and neuropsychological testing, were recruited for this case‒control study. General linear models were used to compare the effective connectivity within the Papez circuit and PVS function between aMCI patients and healthy controls (HCs) and further explore the role of PVS function between the effective connectivity within the Papez circuit and episodic memory. Results The effective connectivity between multiple critical regions within the Papez circuit, notably in the hippocampus, anterior cingulate cortex, and parahippocampal gyrus, was significantly weakened in aMCI patients. Moreover, a significant reduction in the along the perivascular space (ALPS) index was observed among aMCI patients, accompanied by a marked increase in PVS volume, indicating significant PVS dysfunction. Further moderation analysis revealed that PVS function moderated the relationship between effective connectivity within the Papez circuit and episodic memory. Conclusions The effective connectivity within the Papez circuit and PVS function are closely related to cognitive function, particularly episodic memory, and enhancing PVS function may serve as a novel therapeutic target for slowing cognitive decline.